2023
DOI: 10.1101/2023.09.12.556286
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ether phospholipids modulate somatosensory responses by tuning multiple receptor functions inDrosophila

Takuto Suito,
Kohjiro Nagao,
Xiangmei Deng
et al.

Abstract: Transient receptor potential (TRP) and PIEZO channels are known receptors for physical stimuli such as temperature and mechanical touch in sensory nerves. Since these receptors are localized in the plasma membrane, the regulation of sensory receptor activity by plasma membrane lipids has recently attracted attention. In this study, we focused on ether phospholipids (ePLs), which are abundant in neurons, and analyzed their role in somatosensation usingDrosophilaas a model. Reduced warmth avoidance was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Recently, an effect of ether phospholipids on TRPA1 channel activity was demonstrated. Drosophila lacking the gene encoding AGPS, an enzyme involved in ether lipid synthesis, exhibit abnormalities in sensation of hot temperatures that results in an increase in preferred temperature ( Suito et al, 2023 ). Suppressing AGPS expression in TRPA1-expressing neurons also produces similar phenotypic patterns.…”
Section: Membrane Lipids As Modulators Of Thermosensitive Trp Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an effect of ether phospholipids on TRPA1 channel activity was demonstrated. Drosophila lacking the gene encoding AGPS, an enzyme involved in ether lipid synthesis, exhibit abnormalities in sensation of hot temperatures that results in an increase in preferred temperature ( Suito et al, 2023 ). Suppressing AGPS expression in TRPA1-expressing neurons also produces similar phenotypic patterns.…”
Section: Membrane Lipids As Modulators Of Thermosensitive Trp Channelsmentioning
confidence: 99%
“…Electrophysiological analysis using TRPA1 expressed in Drosophila cell lines showed that ether lipids can alter the activation temperature threshold of TRPA1 channels. Ether lipids alter membrane tension and lipid order phase of cell membranes ( Suito et al, 2023 ). Thus, the physicochemical properties of cellular membranes may determine sensory properties.…”
Section: Membrane Lipids As Modulators Of Thermosensitive Trp Channelsmentioning
confidence: 99%